ANALISIS PENGARUH IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY PT X DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Ramadhani, Nathania Eda; Shofwan, Shofwan (Journal of Development Economic and Social Studies, 2022)
Corporate Social Responsibility (CSR) is required by law in Indonesia, and State-Owned Enterprises (SOEs) are no exception. One of the social responsibility programs in the village is the Village Economic Center (Balkondes) program. The collaboration between the Ministry of SOEs and several SOEs is behind the construction of Balkondes. The background of making Balkondes is also based on the not yet maximized village income every year. In fact, when viewed from the side of the location, the village around Borobudur Temple has the potential to be developed into a tourist area that is able to complete the tourist experience when visiting Borobudur Temple. This study provides a perspective on the effect of CSR programs in improving people's welfare. In this study, the multiple regression analysis model was used for data analysis in the form of a Likert scale. Data has been collected through the distribution of questionnaires to the beneficiaries of the Balkondes. The results of the data analysis show that the variables of program objectives, monitoring, and sustainability have a significant positive effect in improving people's welfare. While the variables of community participation and targeting accuracy have a significant negative effect in improving community welfare.